2018
DOI: 10.1111/ijd.13932
|View full text |Cite
|
Sign up to set email alerts
|

The in‐hospital burden of hidradenitis suppurativa in patients with inflammatory bowel disease: a decade nationwide analysis from 2004 to 2014

Abstract: This large-scale study strengthens the evidence that these two inflammatory conditions are truly associated and establishes their joint effect on overall morbidity, mortality, and resource utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 15 publications
(36 reference statements)
1
26
0
2
Order By: Relevance
“…The 3% prevalence of comorbidity in inflammatory bowel disease (441 cases in 13,548 patients) indicates a higher occurrence than in the Swedish population, even if the aggregated reference data did not allow for age-or sex-adjusted comparison. This finding is in line with inflammatory bowel disease being a frequently reported comorbid condition in patients with HS and with the suggested common mechanism of disease [1,5,21]. The 8% prevalence of type 2 diabetes reflects the previously reported comorbidity in metabolic syndrome [1,2,8].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The 3% prevalence of comorbidity in inflammatory bowel disease (441 cases in 13,548 patients) indicates a higher occurrence than in the Swedish population, even if the aggregated reference data did not allow for age-or sex-adjusted comparison. This finding is in line with inflammatory bowel disease being a frequently reported comorbid condition in patients with HS and with the suggested common mechanism of disease [1,5,21]. The 8% prevalence of type 2 diabetes reflects the previously reported comorbidity in metabolic syndrome [1,2,8].…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, HS is more common in women (> 2: 1 ratio) and usually presents after puberty, something which could also be shown in a recent big American study [4]. Inflammatory bowel disease [5] and metabolic syndrome, including type 2 diabetes [6], are frequently reported comorbid conditions in patients with HS. Overweight, obesity, and smoking are associated with HS, and have been shown to correlate with the severity and prognosis of the disease [7,8].…”
Section: Introductionmentioning
confidence: 62%
“…Interestingly, for both Crohn’s disease and ulcerative colitis the risk of new-onset disease was significantly increased among patients with HS. Most recently, a 2018 retrospective cohort study (Bonomo et al, 2018) investigated the in-hospital burden of HS patients with inflammatory bowel disease (IBD) and found that HS patients with IBD were significantly younger and predominantly African American females. These individuals were significantly more likely to be smokers, to be obese, and to have diabetes mellitus, depression, and anemia.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] The onset of HS typically occurs after puberty, 9 and young females are more likely to be affected. 10,11 While variations in the prevalence between different sexes and ages in HS are documented in literature, race-specific prevalence has started to garner attention from the scientific community. 12 Recently, studies examining HS race-specific prevalence concluded that the majority (66.7%) of those affected by HS are Caucasians.…”
Section: Introductionmentioning
confidence: 99%